The status of energy monitoring in science and industry by the example of material handling processes - Fekete, Patrick; Martin, Steve; Kuhn, Katja; Wright, Nicholas (Business, Management and Economics Engineering, 2014)
Global mega trends attract increased resource preservation as well as system efficiency and arouse growing scientific, industrial and public attention, whereas process and technologic developments still lack realisation due to inaccurate knowledge of real process energy demand, associated possible savings and a low inducement for investment. This investigation develops a generally applicable process for energy data collection focussing on material handling systems based on a predefined target model for energy monitoring in order to generate a valid reference model. The introduction of Standardised Energy Consuming Activities (SECA) model enables the development of energy based process functions as reference for its implementation to energetic investigations in various industrial applications. Analysing current and target state of energy monitoring in scientific and industrial investigations for logistics shows the developmental deficit of standardisation and realisation in energy monitoring.